The COD removal in chemical laboratory wastewater by using sugarcane bagasse-activated carbon - Sawasdee, Suchada; Chankerd, Hathairat; Pannasri, Wiroon; Watcharabundit, Prachart (RMUTSB ACADEMIC JOURNAL, 2018)
Chemical oxygen demand (COD) has been the crucially problematic parameter in chemical laboratory wastewater. This study was conducted to investigate the COD adsorption onto activated carbon prepared from sugarcane bagasse in batch process. The effects of adsorption such as contact time (5-240 min) and adsorbent dose (0.5-5.0 g) were evaluated. The adsorption reached the equilibrium at 120 min and the percentage of adsorption increased with increasing adsorbent dose. The equilibrium adsorption data were analyzed using Langmuir and Freundlich adsorption isothermat 30 ºC. It was found that the adsorption correlated well with the Langmuir model and the maximum monolayer adsorption capacity was 29.15 mg/g. The kinetic data followed pseudo-second order model. The study revealed that the activated carbon prepared from sugarcane bagasse can be used as an adsorbent for the removal of COD in chemical laboratory wastewater.